TINJAUAN HUKUM ISLAM TERHADAP SISTEM PENGHITUNGAN PROFIT SHARING DALAM INVESTASI SYARIAH - HSB, Putra Halomoan (Ahkam: Jurnal Hukum Islam, 2017)
Articles talking about the association of funds for invested to a third party a profit sharing mudharabah, by using the method revenue sharing in computation the income bank (gross profit), not profit, received bank or income a bank after reduced costs operational bank ( net profit ).On the other side determining the the percentage the ratio of the without any do not bargain with investors at the beginning of transactions and is not fixed in year.It is performed by the bank consider a level playing bank, excess / lack of funds operational banks and these income bank.Islamic law give freedom to one of the two sides to determine the calculation of a share of the revenue and extraction of the ratio of the them during these based on mutual consent each and does not contain any the forbidden and wombs lawful. The requirement is does not fail in the provisions common way.Keywords: Islamic Law, Profit Sharing, Investment Syariah.